Cyclic degradation in bamboo-like Fe–Mn–Al–Ni shape memory alloys — The role of grain orientation. (15th March 2016) - Vollmer, M.; Krooß, P.; Kriegel, M.J.; Klemm, V.; Somsen, C.; Ozcan, H.; Karaman, I.; Weidner, A.; Rafaja, D.; Biermann, H.; Niendorf, T.
Abstract: In the present study the cyclic deformation behavior within differently oriented grains in Fe–34.8Mn–13.5Al–7.4Ni (at.%) shape memory polycrystals featuring a bamboo-like structure was investigated. In cyclic tensile tests up to 50 cycles, the degree of degradation in pseudoelasticity was evaluated and contributing elementary mechanisms are discussed. The results reveal rapid cyclic degradation in the bamboo-like samples. The unexpected stabilization of parent phase in reverse transformed areas and the proceeding activation of new martensite variants in subsequent cycles were found to be the prevailing degradation mechanisms. Dislocation activity is found to be the most detrimental factor. Graphical abstract: